Sistem Deteksi Api Berbasis Internet Of Things Untuk Mencegah Terjadinya Kebakaran Rumah - Muhammad Dhedy Dwi Putra; Rully Pramudita (Media Jurnal Informatika, 2021)
Along with the times, the use of electricity is also increasing due to the use of electronic goods which are a necessity in this modern era which can be one of the factors that cause fires in the house, the factors for the occurrence of fires are natural factors, namely earthquakes, lightning strikes , volcanic eruptions, and drought, while the human factor itself is the installation of poor electrical installations at home can result in short circuits and cause fires, starting fires in places that are easy to trigger fires such as starting fires near fuel (gasoline) storage, using equipment cooking, and forgetting to unplug electronics when traveling. Therefore, in writing this thesis the title taken is Internet of Things-Based Fire Detection System to Prevent House Fires made using the Prototype Method, the system created is expected to help overcome or prevent fires in people's homes, as well as provide information to homeowners who is going to the smartphone owner of the house, and also sounds the fire alarm so that residents or residents around the house know that the house is on fire, so that residents can evacuate their belongings and can also help extinguish the fire in the house, because The density of housing or settlements in the city of Bekasi is very possible for the potential for fires to occur, and also to reduce the spread of Corona Virus 19 (Covid-19), this research was conducted at Wahana Harapan Housing Block D1 No.15.